Aqueous Zirconium‐MOF Synthesis Assisted by α‐Cyclodextrin: Towards Deeper Understanding of the Beneficial Role of Cyclodextrin. Issue 2 (14th December 2021) - Hoyez, Guillaume; Rousseau, Cyril; Rousseau, Jolanta; Saitzek, Sébastien; Ponchel, Anne; Monflier, Eric
Abstract: A series of isoreticular zirconium‐organic frameworks based on the UiO‐66 family have been synthesized through a co‐modulated hydrothermal method. Our synthetic approach relies on the use of α‐cyclodextrin to co‐modulate the textural properties of the UiO‐66 analogues. We have undertaken a systematic study aiming at exploring how the addition of α‐CD to the reaction mixture can affect or not the properties of UiO‐66 Zr‐MOFs, choosing various substituted benzene‐1, 4‐dicarboxylic acids and pyridine‐2, 5‐dicarboxylic acid as representative organic linkers. The proportion of α‐CD with respect to each ligand can be easily tuned during synthesis, and depending on the chemical structure of the ligands, the oligosaccharide is found to substantially impact the characteristics of the UiO‐66 derivatives. A rationale is proposed to explain the crucial role that α‐CD plays, considering that one of the key parameters is the water solubility of the organic linkers. Abstract : The addition of α‐cyclodextrin has been studied in the hydrothermal synthesis of Zr‐MOFs of the UiO‐66−R topology. Its beneficial impact is shown to be inversely proportional to the solubility of the aromatic dicarboxylic acid linker used upon the cyclodextrin‐assisted synthesis.